Analyzing the Suitability of Cambridge ESL Textbook for Grade IX with K-13 - Hendra Nugraha (Linguistic, English Education and Art (LEEA) Journal, 2022)
Learning objectives act as a pivotal role in education. Learning objectives can be discovered in students’ textbooks which are implemented into learning activities to achieve the objectives of learning. As a result, textbooks should be able to follow a particular standard of curriculum and for Indonesia, it’s K-13. The objective of this study is to analyze the suitability of the learning objectives in the Cambridge ESL Textbook with basic competencies of K-13 for grade IX. Qualitative and library research methods are performed in this study. The researcher utilized content analysis for the textbook and interviews of two sources who use Cambridge textbooks as the research instruments. The result of the study uncovers that 6/11 of learning objectives found in Cambridge ESL Textbook are suitable with basic competencies of K-13 for grade IX. Two sources explained that the textbook has fulfilled the basic competencies of K-13. Upon finishing the study, it is expected that the teacher team or academic manager should be able to determine which textbook to use by considering the suitability of a textbook to a particular curriculum. It also gives an illustration concerning how to achieve the learning objectives of education. Keywords: learning objectives, K-13, and suitability